Preparation of Nanofibers with Renewable Polymers and Their Application in Wound Dressing - Ying Zhao; Yihui Qiu; Huanhuan Wang; Yu Chen; Shaohua Jin; Shuseng Chen (International Journal of Polymer Science)
Renewable polymers have attracted considerable attentions in the last two decades, predominantly due to their environmentally friendly properties, renewability, good biocompatibility, biodegradability, bioactivity, and modifiability. The nanofibers prepared from the renewable polymers can combine the excellent properties of the renewable polymer and nanofiber, such as high specific surface area, high porosity, excellent performances in cell adhesion, migration, proliferation, differentiation, and the analogous physical properties of extracellular matrix. They have been widely used in the fields of wound dressing to promote the wound healing, hemostasis, skin regeneration, and treatment of diabetic ulcers. In the present review, the different methods to prepare the nanofibers from the renewable polymers were introduced. Then the recent progress on preparation and properties of the nanofibers from different renewable polymers or their composites were reviewed; the application of them in the fields of wound dressing was emphasized.